The Role of the Capital Market in Defense Industry Funding from the Perspective of Benefit and Risk Analysis - Cucun Cunayah; Sri Sundari; Suwito (PT FORMOSA CENDEKIA GLOBAL, 2025)
The defense industry requires significant funding to achieve self-sufficiency and reducing reliance on imported defense equipment. This research aims to analyze the benefits and risks if the government considers the option of funding the state-owned defense industry through the capital market. This alternative has been successfully implemented in several countries. This research employs qualitative methods by collecting secondary data obtained through a literature study, including journal articles, books, and research-related sources. The techniques used include data collection, data reduction, data presentation, data analysis, and drawing conclusions. The research results indicate that funding through the capital market offers multiple benefits but also poses potential risks that must be mitigated through a series of appropriate policies to safeguard the country's strategic interests.